The Effect of Harvesting and Replanting on Arthropod Ground Predators in Florida Sugarcane - Ronald Cherry; Robert Gilbert (EDIS)
The population dynamics of arthropod ground predators such as ants, spiders, and beetles have important implications for Integrated Pest Management strategies in sugarcane, and may be indicative of the stability of the Florida sugarcane ecosystem. This fact sheet summarizes the effects of sugarcane harvesting and planting on these predators during a one-year study. This document is ENY-696, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: January 2004.